Recycling and Reuse of Study Materials Among Students in a Malaysian Private University: A Circular Economy Perspective - Izzati Ramli, N. (IEEE Computer Society, 2021)
The idea of circular economy is to sustain the environment by reusing existing materials if it maintains the materials hold its value. The concept of circular economy has gained tractions among business organizations but seldomly studied in the context of institute of higher learning. The concept of 3R (Reuse, Reduce and Recycle) are in line with the principal of circular economy. At universities, students dispose their study materials such as notes, textbooks, coursework materials and others in various ways every semester. Burning lecture notes, throw it away in trash bins or giving it away to their juniors are some of the common ways. Students are aware of the importance of recycle and reuse their study materials but their actions on recycle and reuse is still lacking. This study attempts to identify the student's perception and challenges on adopting a circular economy approach on printed study materials such as lecture notes, quizzes, tests, and others. A survey had been distributed to students from Universiti Teknologi PETRONAS to seek their perception and behavior towards recycling and reusing of study materials. Based on the findings from the survey, the design of a mobile application, called EcoCycle, that facilitates the recycling and reusing activities is proposed. The findings indicated that less than half of the respondent dispose their study materials in the recycling bin and a slightly more than half of the respondent give their study materials to their friends. The existing 3R efforts are done without the assistance of technology and majority of the respondents agree that technology plays an important role in reusing, reducing, and recycling study materials. Â© 2021 IEEE.